Mental health professionals' perspective on a brief transdiagnostic psychological intervention for Afghan asylum seekers and refugees. Issue 1 (31st December 2022) - Knefel, Matthias; Kantor, Viktoria; Weindl, Dina; Schiess-Jokanovic, Jennifer; Nicholson, Andrew A.; Verginer, Lucia; Schäfer, Ingo; Lueger-Schuster, Brigitte
ABSTRACT: Background: While many elaborated treatment protocols focus on post-traumatic stress symptoms, a large number of refugees suffer from a range of mental health problems. Thus, brief and transdiagnostic psychological interventions may be helpful first interventions for help-seeking refugees and asylum seekers in a stepped-care approach. Critically, there is limited research on how transdiagnostic interventions are received in general practice in non-specialized mental healthcare settings in high-income countries, where often only mental health professionals (MHPs) are legally allowed to treat people with mental disorders. MHPs may thus deliver such interventions, but their perspective towards them has not yet been investigated. Objective: We aimed to investigate MHPs' perception of the usability of adapted Problem Management Plus (aPM+), a brief transdiagnostic psychological intervention for refugees, which we adapted to address distress caused by post-migration living difficulties (PMLDs). Method: Employing an e-learning tool, we introduced the aPM+ intervention to 59 MHPs and assessed their perspective towards the intervention. We then used an inductive approach to analyse their perspective towards the intervention with open-ended questions. Results: Altogether, 59 MHPs enrolled in the webinar and 29 provided feedback on the intervention. MHPs had a positive view on the intervention but emphasized the importance of situation-specific adaptations to the structure of the manual. The most favoured specific strategies were 'managing stress/slow-breathing', the 'tree of capabilities', and the 'riding the anger' exercise. The last two were additionally developed to reduce distress caused by PMLDs by either enhancing self-efficacy or reducing anger regulation difficulties. Conclusions: An adaptation to aPM+ regarding more flexibility of the manual may enhance the likelihood of MHPs implementing the intervention in their daily practice. Strategies addressing coping with PMLDs could be particularly helpful. Trial registration: German Clinical Trials Register identifier: DRKS00016538 . HIGHLIGHTS: Mental health professionals had a positive view on a brief transdiagnostic psychological intervention for refugees but emphasized the importance of situation-specific adaptations to the structure of the manual. Low -intensity interventions may be useful not only in low- and middle-income countries but also in high-income countries as part of a stepped-care approach, even if distributed by MHPs instead of trained laypersons.